THE ISLAMIC COMMUNICATION STRATEGIES OF THE NATIONAL AMIL ZAKAT AGENCY (BAZNAS) MAKASSAR IN PUBLIC SERVICE - Mappaselleng, Nur Setiawati; Abu, Roziya; Karim, Bisyri Abdul; Rosmiati, Rosmiati (Balai Penelitian dan Pengembangan Agama Makassar, 2024)
This study aims to identify the Islamic communication strategies implemented by the National Amil Zakat Agency (BAZNAS) Makassar and to assess the community’s response to this communication model. The research utilizes Islamic communication theory, which is grounded in the Quran and Hadith, focusing on the morality of the communicator, the content, and the ethics of communication. The study adopts a mixed-method approach (qualitative and quantitative). Descriptive analysis was conducted throughout the research process to draw conclusions. The results reveal that the Islamic communication strategies applied by BAZNAS Makassar adheres to the core functions of Islamic communication, which include conveying information, socializing, reminding, guiding, motivating, and convincing the public about the importance and benefits of zakat, infaq, and alms (ZIA). Furthermore, the delivery of messages incorporates the principles of qaulan ma'rufan, qaulan kariman, qaulan maysuran, qaulan balighan, and qaulan sadidan, along with other Islamic communication ethics. The impact of this approach has led to high levels of public satisfaction with BAZNAS’s communication methods and models, which are perceived as effective in conveying Islamic values. This model has also increased public trust in the transparency and accountability of ZIA management in Makassar City, thereby enhancing community participation. Keywords: BAZNAS Makassar, infaq and alms, islamic communication strategies, zakat management